The Effect of Current Ratio, Debt to Equity Ratio, Total Asset Turnover, and Return on Assets on Firm Value - Masruro Masruro; Lilik Mardiana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
In this study, we will look at the food and beverage subsector companies listed on the Indonesia Stock Exchange for the period of 2023–2024 to see how the Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Return on Assets (ROA) affect company value, as measured by Tobin's Q. Using secondary data culled from company financial filings, this study employs a quantitative technique. The research sample consisted of 61 firms selected through deliberate sampling. Multiple linear regression using SPSS was the analytical approach employed. It turns out that four metrics Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Total Asset Turnover (TATO) have a major impact on company value simultaneously. However, the partial test results indicate that ROA is the only ratio that significantly affects company value; CR, DER, and TATO have no such effect. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic Growth SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 16: Peace, Justice and Strong Institutions